2013
DOI: 10.1007/s11356-013-2316-3
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in size-fractionated particulate matter in a Portuguese hospital: exposure risks assessment and comparisons with other countries

Abstract: Hospitals are considered as a special and important type of indoor public place where air quality has significant impacts on potential health outcomes. Information on indoor air quality of these environments, concerning exposures to partic-ulate matter (PM) and related toxicity, is limited though. This work aims to evaluate risks associated with inhalation exposure to ten toxic metals and chlorine (As, Ni, Cr, Cd, Pb, Mn, Se, Ba, Al, Si, and Cl) in coarse (PM2.5-10) and fine (PM2.5) particles in a Portuguese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 68 publications
2
18
0
1
Order By: Relevance
“…This is also confirmed by literature data presenting the results of other investigations (Slezakova et al 2014). A high content of As (91.91%), Pb (86.57%) and Cd (77.66%) in PM2.5 mobile fractions in an industrial area in China is also presented by the research of Li et al (2015).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is also confirmed by literature data presenting the results of other investigations (Slezakova et al 2014). A high content of As (91.91%), Pb (86.57%) and Cd (77.66%) in PM2.5 mobile fractions in an industrial area in China is also presented by the research of Li et al (2015).…”
Section: Resultssupporting
confidence: 90%
“…The problem with the assessment of health risk due to the impact of mobile forms of toxic and carcinogenic elements in various fractions of particulate matter in the world is raised only sporadically (Fernández Espinosa et al 2002; Infante and Acosta 1991). In this work, the health risk assessment has been based on a US EPA model (H. Li et al 2015; Slezakova et al 2014; Sun et al 2014; Wiseman and Zereini 2014), which contains an exposure evaluation and risk characteristics. The assessment of the impact of the forecasted exposure to mobile forms of the examined carcinogenic and toxic elements contained in PM1 in the surroundings of coking plants (K1–K4) was conducted on the basis of the results of chemical fractionation based on sequential extraction.…”
Section: Resultsmentioning
confidence: 99%
“…We must also account the 332 fact that exposure to metals occurs also via ingestion and dermal contact and, if these routes are 333 considered, the estimated risks might be higher (Slezakova et al, 2013). …”
mentioning
confidence: 99%
“…7 Both temperature and relative humidity were the recommended indices to reflect the efficiency of ventilation systems in hospitals. 13 The most important index for evaluating indoor air quality was CO 2 concentration, since it was correlated with both number of persons in a space and the PM concentrations, 14,15 and was significantly related to airborne bacterial count.…”
Section: Introductionmentioning
confidence: 99%
“…7,[23][24][25][26][27][28] Slezakova et al 7 found high averaged 24-h particulate matter (PM 10 and PM 2.5 ) in a Portuguese hospital. Moreover, a previous study found that 90% of CO 2 samples in the ICU of a medical center in northern Taiwan exceeded 1,000 ppm, and 20% of PM 2 samples failed to meet the air quality standard set by the United States Environmental Protection Agency (EPA).…”
Section: Introductionmentioning
confidence: 99%